Participatory approach in designing a One Health rabies surveillance form for integrated bite case management in Uganda - Okech, Samuel George; Ghimire, Rabina; Odoch, Terence; Hartnack, Sonja; Agado, Doreen; Akankwatsa, Dickson; Apio, Felister; Babirye, Priscilla; Lunkuse, Stella Maris; Nakanjako, Maria Flavia; Opolot, John; Lohr, Frederic; et al. (Frontiers in Tropical Diseases, 2025)
IntroductionRabies, a neglected viral zoonotic disease endemic in Uganda, is one of the country’s top seven priority zoonotic diseases. In the period 2021 to 2024, it caused 190 human deaths. Rabies requires an integrated participatory One Health approach for its control. This approach may help reduce the estimated 59,000 annual global human rabies deaths. Over 99% of these deaths are due to bites from infected dogs. Access to the highly effective post exposure prophylaxis (PEP), mass dog vaccinations and rabies surveillance are prioritised in Uganda’s National Rabies Elimination Strategy that is aligned to the global target of eliminating dog-mediated rabies by 2030. Surveillance, required to guide and evaluate rabies control, is currently weak in Uganda, resulting in few cases being recorded. This leads to a “cycle of neglect” of the disease. Medical and animal health professionals require comprehensive surveillance data to inform post-bite responses. An integrated bite case management (IBCM) system presents the opportunity for information about the bite victim and biting animal to be obtained timely to support judicious and economical use of PEP in humans and management of the biting animal. IBCM has not yet been tested in Uganda where PEP is scarce.MethodsA collaborative change research approach was therefore applied to progressively develop key elements of an IBCM form over three successive multidisciplinary and multi-sectoral stakeholder meetings, which noted that to attain effective joint surveillance, both animal- and human-related information should be obtained from an animal bite incident.Results and DiscussionStakeholders identified elements that were grouped under five categories: details of the human bite victim, details of the bite incident, details of biting animal, follow-up of the biting animal and laboratory diagnosis. Four existing rabies surveillance tools in the country were assessed against these categories. The process revealed gaps in the tools currently in use by government ministries hence exposing the silo system in rabies surveillance. This paper highlights the rich content of an IBCM form designed through a stakeholder participatory process, and its advantages over existing tools regarding data collected. It is hoped that its implementation will significantly strengthen joint human and dog rabies surveillance in Uganda.